City Nicknames on the Island of Java for Strengthening Urban Identity: Study of Toponymy - Oktaviana, Ika; Baiti Lapiana, Ummi Nurjamil; Sekar Kasih, Arum Rindu (MIMESIS, 2026)
The Island of Java is an island of diverse range of cities, each with its own unique characteristics that are embedded in various aspects of daily life. One fascinating aspect of these cities is their distinct nicknames, which serve as a reflection of their individual identities. The study aims to delve into the origin-based meanings of these nicknames, investigating the historical, cultural, geographical, and social factors that have contributed to their formation. This qualitative descriptive research aims to delve into the intricate factors that contribute to the formation of these city nicknames on the Island of Java.  The data for this study consists of nicknames for cities on the Island of Java that is taken from the book sources which were then analyzed by the theory of naming and referent. The study discovers a multitude of contributing elements, including culinary, natural resources, human resources, historical significance, climatic conditions, industrial prowess, and artistic expressions. The study findings illuminate that these city nicknames are forged from the most remarkable and exceptional attributes that set them apart from other cities. This exceptionalism plays a pivotal role in forging the city's identity, thus drawing people to explore its culinary delights, appreciate its natural allure, and delve into its rich history and arts. Consequently, these diverse elements collectively weave a tapestry of vibrant and multifaceted identities for Java’s cities.